TOPOLOGY OF ENTREPRENEURIAL UNIVERSITY: STATIC DESCRIPTIVE MODEL - R. A. Zayakina (Высшее образование в России)
The article offers a topological perspective on social networks created by universities, which are oriented towards commercialization ofintellectual activity and promotion ofin-novation. The perspective is based on the achievements of social topology as well as application of the basics of mathematical topology and methodology for building ideal-type constructs. The author reveals theoretical and methodological fundamentals of the procedures for establishing real network design, which is considered one of the algorithms of social topology application in the framework of network approach. Real network design rests upon identification of informational blocks called network descriptors, which, in their turn, are divided into static and dynamic ones. The present article centres upon static descriptors, which are divided into identification and structural descriptors. A set of their characteristics is described. The networks with university participation are studied with regard to the applied methodology. The author outlines the features, which are necessary for effective creation of innovative ecosystem of a university.